A TRIBUTE TO PIONEERS OF PAFMJ: Pioneers of PAFMJ - Akhtar, Mahmud Ahmad (Pakistan Armed Forces Medical Journal, 2009)
A TRIBUTE TO PIONEERS OF PAFMJAn editorial titled “Fourth Regional Conference on Medical Journals in the Eastern Mediterranean Region” was published in the March 2009 issue of Pakistan Armed Forces Medical Journal [PAFMJ] in which the retrospective data of articles in various disciplines or specialties published in PAFMJ from 1956 – 2005 was analysed. The data suggest that a very large number have been published in the last decade [1996 – 2005] compared to the three earlier decades i.e 1956 – 1965, 1966 – 1975, 1976 – 1985. I think this conveys an erroneous impression. If we take into account the fact that there is a much larger number of specialists, sub-specialists, medical institutions now available as well as medical equipment, para-medical staff, ancillary support and funding, the number of articles per capita actually indicates substantial decline.I would like to draw your attention to the following facts:-• Decade [1956 – 1965]: The PAFMJ was launched just after a couple of years Pakistan came into existence in 1947. It was a period of rehabilitation and establishment of institutions. I salute the solid contributions made by our great teachers and pioneers in the field of clinical practice, research and publication. High quality-pioneer research was done in many fields, like liver biopsies, histopathological studies of viral hepatitis, typhus, virology and surgery etc. During this period, the disciplines of basic medical sciences like Anatomy, Physiology, Biochemistry, Pharmacology, Forensic Medicine did not exist in the Army Medical Corps [AMC]. Even the Department of Pathology had very few appropriately trained Pathologists. Armed Forces Institute of Pathology [AFIP], the Alma Mater of Pathologists of AMC had only four or five Pathologists on its strength and the Commanding Officer was of the rank of Lieutenant Colonel. CMH Lahore, PNS Shifa Karachi and CMH Peshawar had only one Pathologist each. Many Pathologists were graded specialists. In those days, I was serving in CMH Jhelum as a Medical Specialist and the hospital had no Pathologist on its strength and I had to supervise the lab and also perform the duties of the staff surgeon.In that decade [1956 – 1965], 15 articles were published by this small number of Pathologists. During the recent past decade [1996 – 2005], only 110 articles have been published while, the number of Pathologists has increased thirty-fold this making a ratio of 1:30, the articles should have been 450 in the decade 1996 – 2005. Thus, proportionally, the number of publications has decreased considerably.• In Medicine, Rawalpindi station during the decade [1956 – 1965] had only one classified medical specialist and a few part-time graded specialists on its strength. Federal Government employees were also dependent for medical treatment on the Military Hospital. CMH Peshawar had only one medical specialist who used to provide medical cover to CMH Nowshera, CMH Risalpur, CMH Kohat. Similarly, CMH Lahore and PNS Shifa Karachi had one medical specialist on its strength. CMH Quetta had just a graded specialist on their rolls while many other hospitals [CMH’s] didn’t have any.Furthermore, there were no super or sub-specialists at all. No Pediatrician was available in that era. At many stations, there were no Dermatologists and Psychiatrists. The medical specialist had to perform all their duties. Medical specialists from the decade [1956 – 1965] to the decade between [1996–2005] have increased 40 fold. The number of articles published in Medicine, including Cardiology and Pediatrics during [1956 – 1965] is 62, whereas, during the decade between [1996–2005] is 140. With a 40-fold increase in numbers the articles should have been about 2500. Proportionately, the trend of publishing articles in Medicine has declined enormously.• Take the discipline of Surgery. The situation was even worse. Hardly a few surgeons were available during the decade of [1956 – 1965] but they published 28 articles. These increased to 56, i.e double during the decade of [1996 – 2005], whilst, the number of surgeons has increased about forty times in AMC. The number of articles during the decade [1996 – 2005] should have been over eleven hundred. [It is evident that the number of articles published in the past per each surgical specialist was much more than today].• Similarly is the situation in Ophthalmology, Otolaryngology and Dermatology. The number of publications in these disciplines in decade of [1996–2005] is less as compared to published those during [1956 – 1965] considering the articles published per specialist.• Secretarial and financial help in earlier days was meagre. PAFMJ was published form Armed Forces Medical College [now AFPGMI] in those days. There were only 6-7 Officers at AFM College including the Commandant. No clerk or typewriter existed. The authors used to type the articles themselves on manual type-writers. Occasionally a part-time clerk was made available. Funds were scarcely available. There was no librarian in the AFM College. The wife of Commandant, Col Jilani [an English lady] opted to work day and night and that too in honorary capacity. She established the library with the help of only one part-time laboratory technician. Her’s was indeed a remarkable contribution.Virtually, there were no holidays or week-ends or privilege leave in that era. Specialists had to attend day / night patient calls, and they also performed DMOS and field duties. It is crystal clear that the performance of the specialists was of an exceptionally high order keeping in view the human and material resources available compared to today. In [1956 – 1965], AMC was a leading medical facility in the country. Now it is sadly not so. I have observed few presentations of a high order in the conferences to-day compared to those in the past. It may also be borne in mind that when during [1947 – 1965], two Kashmir Wars broke out and another war in 1971, the AMC Officers moved to the border and field area[s] and PAFMJ became almost non-functional.A depressing aspect of publication is in the field of nutrition. During [1968 – 1975], 23 articles were published. During [1996 – 2005], only four articles have been published. During the decades following the 1956 – 1965 periods the situation was also much better than 1996 – 2005.In conclusion, the aim to publishing the Corps Journal is to promote continuing medical education. It should contain material on the latest development as well as abstract from other well-respected Journals of specialists and senior doctors should give a lead in writing well researched articles. We should pay a just tribute to our forerunners in AMC who pioneered articles and worked with zeal, zest, devotion and dedication.They are our role models. We owe them so much. Now that knowledge has expanded so much and so much information is available at our fingertips, both the quantum and the quantity of articles published in the Journal should expand and young medicos should be encouraged to write well-researched articles. There is a dire need to have research degrees in clinical subjects as is the practice in the U.K. Lt Gen ® Mahmud Ahmad Akhtar, HI[M]Former Surgeon General Pakistan Army& DGMS[IS]43 – Race Course Road, Rawalpindi